Witchcraft narratives in Germany : Rothenburg 1561-1652 - Rowlands, Alison (Studies in early modern European history., 2003)
This text looks at why witch-trials failed to escalate into 'witch-crazes' in certain parts of early modern Europe. Using the legal records of Rothenburg ob der Tauber, the book explores the social and psychological conflicts behind the making of accusations and confessions of witchcraft.